On the dissonance between the legislature’s actual and declared objectives of shaping the agricultural system - Joanna Mikołajczyk; Ireneusz Nowak (Studia Prawnicze KUL)
At the root of the restrictive legal regulations that were introduced in the Act of 11 April 2003 on Shaping the Agricultural System is the assumption of the special importance of agricultural real estate in the socio-economic system in Poland.